Why does the average price paid fall during high demand periods? - Aviv Nevo; Konstantinos Hatzitaskos (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2006)
For many products the average price paid by consumers falls during periods of high demand. We use information from a large supermarket chain to decompose the decrease in the average price into a substitution effect, due to an increase in the share of cheaper products, and a price reduction effect. We find that for almost all the products we study the substitution effect explains a large part of the decrease. We estimate demand for these products and show the price declines are consistent with a change in demand elasticity and the relative demand for different brands. Our findings suggest, that for the data we examine, loss-leader models of retail competition are not the main explanation for price declines.
Keywords: 330